Income Inequality in Europe Since the Crisis - Michele Raitano (Intereconomics, 2016)
Economic inequalities are engendered by a complex process, characterised by several steps and involving the interaction of several factors. The best indicator of individual economic well-being is disposable equivalised income. Evidence shows that welfare states retain a crucial function in Europe and that they have been central in limiting the detrimental effects of the financial crisis on disposable income distribution.
Keywords: 330; Einkommensverteilung; Verfügbares Einkommen; Wirtschaftskrise; EU-Staaten